Changing Conditions in Personnel Department of Advertising Agencies in India - Sofat, Yashmin (Prabandhan: Indian Journal of Management, 2011)
There has been a little effort to analyze the changing conditions of the workers working in the advertising agencies in India. In this paper, the author attempts to understand the context that how advertising agencies in India formulate their strategies, which helps to gain an insight into know the changing working conditions of the workers in the personnel department. The author tries to clarify that how the strategies of advertising agencies vary across their nature and experience. In this paper, the author has attempted to clarify the strategies that advertising agencies attain, maintain, retain and develop for their human resources, which helps in the reduction of the employees’ turnover.